Post-COVID-19 investor psychology and individual investment decision: A moderating role of information availability - Jan, Naveed; Jain, Vipin; Li, Zeyun; Sattar, Javeria; Tongkachok, Korakod (Frontiers in Psychology, 2022)
This study aims to investigate the influence of psychological biases on the investment decision of Chinese individual investors after the pandemic of COVID-19 with a moderating role of information availability. A cross-sectional method with a quantitative research approach was employed to investigate the hypothesized relationships among variables. The snowball sampling technique was applied to collect the data through a survey questionnaire from individual investors investing in the Chinese stock market. Smart-PLS statistical software was used to analyze the data and for the estimation of hypotheses. Results indicated that overconfidence, representative bias, and anchoring bias have a significant and positive influence on investment decisions during the post-Covid-19 pandemic; however, the availability bias has insignificant and negative effects on the investment decision during the post-COVID-19 pandemic. Moreover, findings indicated that information availability has a significant moderating role in the relationship of psychological biases with the investment decision during the post-COVID-19 pandemic. This study contributes to the body of knowledge regarding behavior finance, psychological biases, and investment decision in emerging stock markets. The findings of the present study improve the understanding that how investors’ psychology affects their investment decisions.